Retroperitoneal extraskeletal osteosarcoma in a dog: a case report - Piedra-Mora, César (2016)
A 15-year-old not neutered mixed-breed dog was presented with hyporexia, constipation, lethargy and abdominal pain. An intra abdominal mass was identified during the physical examination. Mild normocytic and normochromic anemia and leukocytosis due to neutrophilia were detected in the complete blood count. Serum biochemistry results showed alterations in blood urea nitrogen, serum alkaline phosphatase, and creatinine. A splenic nodule was detected during the ultrasonographic examination, and radiographic findings showed a radiopaque area in the abdomen near the lumbar vertebrae. An exploratory laparotomy was done, and two retroperitoneal masses were found. Due to the difficult surgical approach euthanasia was elected. Histopathological and immunohistochemical evaluation of tissues was performed and the diagnosis of extraskeletal osteosarcoma was made. Extraskeletal osteosarcoma is an infrequent malign mesenchymal tumor without primary involvement of bone tissue or periosteum. Seldom has the retroperitoneal localization of this tumor been reported.